The effects of the instrumental reminiscence therapy based on Roy's adaptation model on adaptation, life satisfaction and happiness in older people: A randomized controlled trial - Aydogdu, Ozlem; Tastan, Sevinc; Kublay, Gulumser (Wiley, 2023)
Aim This trial aimed to evaluate the effects of instrumental reminiscence therapy based on Roy's adaptation model on adaptation, life satisfaction and happiness in older people. Background Reminiscence therapy is one of the nursing interventions that facilitates the adaptation of older people to the process of ageing. Design The study utilized a pretest-posttest randomized controlled trial design. Methods This study was conducted at two nursing homes in Northern Cyprus between April and June 2021. The trial comprised 34 participants. A descriptive information form, the Assessment Scale of Adaptation Difficulty for the Elderly, Life Satisfaction Index A and Oxford Happiness Questionnaire-Short Form were used for data collection. Results Mean posttest scores obtained by the intervention group from the Assessment Scale of Adaptation Difficulty for the Elderly, Life Satisfaction Index A and Oxford Happiness Questionnaire-Short Form were significantly higher than their pretest scores (P < 0.05). There was a significant difference between the mean scores obtained by the intervention and control groups from the Assessment Scale of Adaptation Difficulty for the Elderly, Life Satisfaction Index A and Oxford Happiness Questionnaire-Short Form (P < 0.05). Conclusion Instrumental reminiscence therapy based on Roy's adaptation model increased the levels of adaptation, life satisfaction and happiness in older people. Therefore, instrumental reminiscence therapy might be applied, integrated with the Roy's adaptation model.
Keywords: adaptation model; happiness; life satisfaction; nursing; older adults; reminiscence therapy